Optimization of the e-learning system for efficiency of participant registration times at training institutions: Case study at an ESAS management institute - Sutrisna, Eris; Alijoyo, Franciskus Antonius (Universitas Wiralodra, 2024)
Application e-learning technology has become integral to management education and training in various institutions. One of the aspect keys in context is the efficiency of time registration of participants. This article documents studies of cases carried out at the ESAS Management Institute, which aims to optimize the e-learning system to increase efficiency in the time registration of participants. This study integrates qualitative and quantitative methodology to comprehensively understand changes that occur in participants' registration process after the implementation of the e-learning system. Research results show significant improvement in speed registration participants. Queues and times wait participants are reduced, and e-learning systems provide 24/7 availability, eliminating limited time in the registration process. Verification documents become more accurate, reducing the risk of error, man. In evaluating sustainability, participants and staff administration give bait to come back optimistic about change. This article also highlights the importance of data collection and evaluation sustainability in maintaining and improving the efficiency system. This study gives a strong foundation for institutions with other training to optimize their e-learning system for efficient time registration participants. Thus, the article gives a valuable guide in adopting e-learning technology to increase the experience of participants and the efficiency of administrative processes in institutional training.